Phytotoxicity of compost produced with mountain microorganisms and biodigester sludge (UNED Research Journal, 2019)
Introduction: compost quality may be enhanced with compost optimization agents. These agents must guarantee safety. Compost phytotoxicity tests are an economic, rapid and reliable mechanism to detect toxic substances in compost that may inhibit seed germination and plant growth. Objective: to evaluate the phytotoxicity of mountain microorganisms and biodigester sludge as compost optimization agents Methods: complete randomized blocks bioassay with cucumber seeds (Cucumis sativus). Results: individual use of these agents has no inhibitory effects in cucumber germination and growth and is thus safe. However, added simultaneously, they have inhibitory effects on germination and growth of cucumber, possibly from the phytotoxic effect of excess Zinc and Boron. Conclusion: we recommend caution and further tests with additional growth stages and species.
Keywords: quality of organic fertilizer; sustainable agriculture; biofertilization; nutrient cycling.